Apple, Foxconn, and Chinese workers’ struggles from a global labor perspective - Pun, N; Shen, S; Guo, Y; Lu, H; Chan, J; Selden, M (Taylor andamp; Francis (Routledge): SSH Titles, 2016)
To enrich the discussion of global labor, between 2010 and 2016, we studied Apple’s value chain, Foxconn’s mode of labor control, and Chinese workers’ struggles. Through our fieldwork in China we also examined Apple’s and Foxconn’s responses to the spate of worker suicides, workers’ resistance, the activism of scholar and student groups, and transnational justice campaigns. We conclude with reflection on global labor studies in light of the debates between Karl Polanyi’s counter movement and Karl Marx’s class-based struggle.